2018
DOI: 10.1111/jfpe.12822
|View full text |Cite
|
Sign up to set email alerts
|

Local air velocity, a key factor governing the Raclette cheese mass loss in an industrial ripening room

Abstract: Raclette cheeses arranged in racks were ripened in an industrial ripening room under temperature, relative humidity, and air circulation control. Cheese mass loss was investigated via two ripening trials and by weighing nine racks located at chosen places in the ripening room. Air velocity (varying from 0.06 to 0.48 m/s as a function of the distance of the textile ventilation ducts that ensure air circulation) had the greatest effect on mass loss (changing from 4.1 to 8.7% of the initial mass). The higher the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Ventilation could also be optimized with new techniques, such as sequential ventilation. For cheese processing, using this energy efficiency technique is more convenient not only for electricity savings but also because the end-product could have better quality [81], [82].…”
Section: A Energy Savings Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventilation could also be optimized with new techniques, such as sequential ventilation. For cheese processing, using this energy efficiency technique is more convenient not only for electricity savings but also because the end-product could have better quality [81], [82].…”
Section: A Energy Savings Techniquesmentioning
confidence: 99%
“…Most of the processes are complex and difficult to be changed. Moreover, even in some cases the product quality was improved such as the cheese [81], [82], setting parameters modulation to save energy consumption can negatively influence end product quality. Finally, as previously stated, some food production processes are very rigid due to end quality, and hence it is difficult to accommodate renewable energy and energy saving options.…”
Section: B Technologicalmentioning
confidence: 99%
“…Gaucel et al (2012) proposed a generalized model to assess cheese mass loss during ripening of Camembert and Saint-Nectaire cheeses based on the analysis of water activity on the cheese rind and measurements of relative humidity during ripening. Corrieu et al (2018) found that the mass loss in Raclette cheese during ripening was related mainly to local air velocity. However, although the models proposed in the aforementioned studies exhibited goodness of fit and produced useful predictable traits, they cannot be easily applied in the dairy industry, for 2 reasons: (i) the cheese biochemical and physical explanatory variables used to create the predictive models were obtained using time-consuming, high-cost analytical methods; (ii) the predictive models indirectly measured phenomena occurring during the ripening of specific cheeses or specific categories of cheese.…”
Section: Modeling the Evolution Of Cheese Yield During Ripeningmentioning
confidence: 99%